Efektivitas Model Project Based Learning dengan Pendekatan Inkuiri Berbasis Lingkungan terhadap Hasil Belajar IPA - Anggun Zuhaida*; Zaidatul Mubtasyiroh (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Science learning is identical to learning that not only prioritizes understanding concepts but also wants students to carry out experiments both in the surrounding environment and in the laboratory. This study aims to determine the learning outcomes of the project based learning (PjBL) model with an environmental-based inquiry approach of additives and addictive substances and the effectiveness of the PjBL model with a home-based inquiry approach to science learning outcomes. This research is a quantitative research with a quasi-experimental method. The sampling technique was carried out by purposive sampling where the sampling was divided into two classes, namely the experimental class and the control class. The results showed that the learning outcomes in the experimental class had an average posttest result of 67.2 and in the control class had an average posttest result of 60.0, it can be interpreted that the group using this model was successful and the use of the PjBL model with an environment-based inquiry approach was effective on learning outcomes in class VIII students with the results of the t test calculation, namely the value of t count t table that is 6.783 2.045 and probability 0.000 0.05. The learning model in this study is the PjBL-Inquiry model which can be an alternative model that can be applied in learning, to improve students' skills in achieving their main competencies